Acceptability and feasibility of dual HIV and syphilis point-of-care testing for early detection of infection among pregnant women in China: a prospective study. Issue 10 (25th October 2018) - Wang, Qian; Chan, Po-Lin; Newman, Lori M; Dou, Li-Xia; Wang, Xiao-Yan; Qiao, Ya-Ping; Su, Min; Chen, Xiang-Sheng; Jin, Xi; Wang, Ai-Ling
Abstract : Objective: To assess the feasibility and acceptability of using WHO prequalified combined dual HIV/syphilis rapid diagnostic tests (RDT) for same-day results in antenatal care (ANC) clinics. Methods: This is a pragmatic implementation study using quantitative approach to evaluate outcomes. Antenatal clinic attendees from 21 rural and urban township hospitals in two provinces of China were offered with free dual RDTs testing that included HIV and syphilis, in addition to the routine blood tests. Study outcomes included testing uptake before and during dual RDT use, test feasibility and acceptability among pregnant women. Regression model was used to assess acceptance of RDT testing. Results: In total, 1787 out of 1828 pregnant women attending ANC received the RDT testing. Testing uptake among pregnant women in their first and second trimester increased from 76.0% (2438/3269) using standard blood testing to 90.1% (1626/1787) with concurrent RDT use (χ 2 =197.1, p<0.001). Among 1787 pregnant women who received RDT tests, 98.3% (1757/1787) participants were given test result the same day. Positive proportions of HIV and syphilis screened with RDT were 0.06% (1/1787) and 1.0% (18/1787), respectively. Regression analysis indicated that women who did not receive syphilis or HIV testing before were less likely to accept dual RDT (OR 0.28, 95% CI 0.10 to 0.75). Acceptance for dual RDT testing at second or third antenatal visit was lower compared with the first visit (OR 0.37, 95% CI 0.15 to 0.94). Conclusion: Combined dual HIV/syphilis RDT with same-day results increased uptake of HIV and syphilis testing among pregnant women at primary healthcare facilities. Given the diversity of testing capacities among health services especially in rural areas in China, the dual RDT kit is feasible tool to improve testing uptake among pregnant women.